2019
DOI: 10.1073/pnas.1906223116
|View full text |Cite
|
Sign up to set email alerts
|

Trading amino acids at the aphid– Buchnera symbiotic interface

Abstract: Plant sap-feeding insects are widespread, having evolved to occupy diverse environmental niches despite exclusive feeding on an impoverished diet lacking in essential amino acids and vitamins. Success depends exquisitely on their symbiotic relationships with microbial symbionts housed within specialized eukaryotic bacteriocyte cells. Each bacteriocyte is packed with symbionts that are individually surrounded by a host-derived symbiosomal membrane representing the absolute host–symbiont interface. The symbiosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 73 publications
2
73
1
Order By: Relevance
“…For example, bees feed on amino acid rich pollen and ants have a wide range of food sources ( Rabie et al, 1983 ; Nicolson and Human, 2013 ). Another possibility is that symbiotic bacteria can provide essential nutrients to host insects, as reported in Cephalotes ants by Hu et al, 2018 and as well known in other insects such as aphids ( Wilson et al, 2010 ; Feng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 90%
“…For example, bees feed on amino acid rich pollen and ants have a wide range of food sources ( Rabie et al, 1983 ; Nicolson and Human, 2013 ). Another possibility is that symbiotic bacteria can provide essential nutrients to host insects, as reported in Cephalotes ants by Hu et al, 2018 and as well known in other insects such as aphids ( Wilson et al, 2010 ; Feng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 90%
“…They supplement the nutritional requirement of their host by synthesizing essential amino acids and rare vitamins especially for the hemimetabolous sap-sucking insects that feed on nutrient-poor diets. For instance, in Buchnera aphidicola, an obligate symbiont of aphids, and probably the most studied model, it has been shown that the bacteria fulfills the nutritional requirement of the insect host to an extent that its removal dramatically affects aphid survival and fecundity (Feng et al, 2019). Similarly, symbiosis between the sap-feeding insect Megacopta cribraria and its primary bacterial symbiont, Candidatus Ishikawaella capsulate, is essential for host survival to adulthood (Couret et al, 2019).…”
Section: Diverse Forms Of Insect-microbe Associations -From Initiatiomentioning
confidence: 99%
“…However, there may be striking differences between patterns of symbiont-induced host post-transcriptional modifications between mutualists and pathogens. For example, in regards to ubiquitination, amino acid economies are vastly different between pathogenic infections that usurp them from the host (Zhang and Rubin 2013) and mutualistic infections that synthesize them for the host (Feng et al 2019). Thus, if mutualists are capable of altering host ubiquitination, they may be more likely to use it to control host signalling cascades than to obtain amino acids.…”
Section: E Post-translational Modification Of Host Genetic Regulatomentioning
confidence: 99%